2014
DOI: 10.1186/preaccept-9134577561374599
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and symmetric deposition of misfolded tau oligomers within presynaptic and postsynaptic terminals in Alzheimer¿s disease

Abstract: The accumulation of neurofibrillary tangles in Alzheimer’s disease (AD) propagates with characteristic spatiotemporal patterns which follow brain network connections, implying trans-synaptic transmission of tauopathy. Since misfolded tau has been shown to transmit across synapses in AD animal models, we hypothesized that synapses in AD patients may contain misfolded tau. By immunofluorescence imaging of bipartite synapses from AD subjects, we detected tau protein in 38.4% of presynaptic and 50.9% of postsynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…Previous authors reported that glutamate activates CaMKIIα to induce synaptic plasticity (Miller et al, 2002, Coultrap et al, 2014), and that activity-dependent increases in tau protein in excitatory synpases (Frandemiche et al, 2014) represents a physiological mechanism that contributes to synaptic plasticity (Kimura et al, 2013). Notably, tau protein is detectable in postsynaptic terminals in AD brains (Tai et al, 2014); this finding suggests that high AMPA and NMDA receptor stimulation can trigger the aberrant local translation of tau to induce AD pathology. Stress granules are likely to participate in dendritic tau-triggered neurodegeneration since tau is known to interact with the RNA-binding protein T-cell intracellular antigen 1 (TIA1) in stress granules (Vanderweyde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors reported that glutamate activates CaMKIIα to induce synaptic plasticity (Miller et al, 2002, Coultrap et al, 2014), and that activity-dependent increases in tau protein in excitatory synpases (Frandemiche et al, 2014) represents a physiological mechanism that contributes to synaptic plasticity (Kimura et al, 2013). Notably, tau protein is detectable in postsynaptic terminals in AD brains (Tai et al, 2014); this finding suggests that high AMPA and NMDA receptor stimulation can trigger the aberrant local translation of tau to induce AD pathology. Stress granules are likely to participate in dendritic tau-triggered neurodegeneration since tau is known to interact with the RNA-binding protein T-cell intracellular antigen 1 (TIA1) in stress granules (Vanderweyde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We need to address critically to what extent these animal models actually mimic the pathogenesis and pathology of AD in humans, beyond the superficial resemblance of accumulating plaques and tangles, which were artificially driven by overexpressing mutant proteins. For instance, when we first discovered the presence of tau oligomers inside human synaptic terminals [9, 27], we also checked a common animal model of tauopathy, rTg4510 mice overexpressing P301L human mutant tau [28], but its synaptosomes were free of tau oligomers (unpublished data). It is plausible that the mutant tau misfolded so aggressively that they became aggregated before reaching the synapse, causing a marked distinction between mouse and human neuropathology.…”
Section: Human Brain Banksmentioning
confidence: 99%
“…Based on our experience of examining synaptically enriched preparations with electron microscopy, immunofluorescence microscopy [9, 27], flow cytometry, and super-resolution microscopy (unpublished data), with both human and mouse samples, it appears that at least five classes of nerve ending particles can be found (Fig. 2): (I) intact bipartite synapses, which show snowman-like structures; (II) presynaptic terminals with membrane-free PSD attached; (III) presynaptic terminals with membrane-enclosed PSD, but missing much of the postsynaptic cytoplasm; (IV) isolated presynaptic terminals; (V) isolated postsynaptic terminals.…”
Section: Isolation Of Human Synaptosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to amyloid beta, however, the verdict seems to be clearer that neurofibrillary tangles themselves are functionally inert [84, 101, 167] and that soluble tau aggregates mediate synaptic damage [148, 219, 223]. Hyperphosphorylated tau was shown to localize to both pre- and postsynapses in multiple studies [81, 86, 88, 148, 188, 189, 191, 219], where it causes synaptic dysfunction by impairing the trafficking or synaptic anchoring [86] as well as the excitability [130]. In THY-Tau22 mice, which express tau with the G272V and P301S mutations, the synaptic enhancement induced by exogenous BDNF was lost due to impaired NMDA receptor function [28].…”
Section: Intraneuronal Amyloid Betamentioning
confidence: 99%